Challenging the hypothesis of an Arctic Ocean lake during recent glacial episodes. (13th April 2022) - Hillaire‐Marcel, Claude; Myers, Paul G.; Marshall, Shawn; Tarasov, Lev; Purcell, Karl; Not, Christelle; De Vernal, Anne
ABSTRACT: The Arctic Ocean is one of the last frontiers on Earth with many unknowns about its geological and climate history and considerable speculation on its role in the Earth's climate and ocean system. It has been proposed recently that it was occupied by a freshwater body of more than 9.5 × 10 6 km 3 underneath a thick ice mass during part of glacial isotopic stages 6 and 4. We argue that such a dramatic scenario, implying replacement of marine waters by freshwater throughout the entire Arctic Ocean and Nordic Seas, is physically implausible. The very low 230 Th excesses ( 230 Thxs ) observed in sediments from these intervals were used as evidence for the presence of a U‐depleted overlying freshwater column. We show here that they may simply result from short, sporadic sedimentary pulses, below multiyear sea ice or ice shelves, linked to deglacial ice streaming and surging events interrupting long‐duration sedimentary gaps. Due to this sporadic sedimentation regime, interpolating time from 230 Thxs data or between benchmark ages in sedimentary sequences would simply be erroneous.